Handbook of Supply Chain Management - B Ayers, James (CRC Press, 2009)
When you invest millions on new systems you don't want yesterday's solutions. You need a global view of end-to-end material, information, and financial flows. Managers today have the same concerns managers had last year, 10 years ago, or 50 years ago: products, markets, people and skills operations, and finance. New supply chain management processes give managers a hierarchy to the tasks they must perform to deal with these issues.